2017
DOI: 10.1089/bfm.2017.0063
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Components, Including Stem-Like Cells, of Preterm Mother's Mature Milk as Compared with Those in Her Colostrum: A Pilot Study

Abstract: The increased level of these different cell components in mature milk may be important in the long-term preterm baby's health growth. Further similar research in a larger population of various gestational ages and lactation stages of preterm mothers is warranted to support these pilot findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 13 publications
2
10
1
Order By: Relevance
“…It has been suggested that the number of stem cells in human milk may be affected by the maturation of mammary glands at different stages of lactation, and the changes in stem cell populations at different stages of lactation may be consistent with the needs of infants at different stages of growth and development. Kaingade et al (2017) showed that the percentage of mesenchymal stem cells (CD44+, CD90+, and CD105+ cells) was higher in mature milk than in colostrum, but changes in these cells at different stages of lactation were not found in the present study. This disparity may be due to the differences in subjects and methods between the two studies.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…It has been suggested that the number of stem cells in human milk may be affected by the maturation of mammary glands at different stages of lactation, and the changes in stem cell populations at different stages of lactation may be consistent with the needs of infants at different stages of growth and development. Kaingade et al (2017) showed that the percentage of mesenchymal stem cells (CD44+, CD90+, and CD105+ cells) was higher in mature milk than in colostrum, but changes in these cells at different stages of lactation were not found in the present study. This disparity may be due to the differences in subjects and methods between the two studies.…”
Section: Discussioncontrasting
confidence: 88%
“…Major temporal changes in human milk composition occur throughout lactation, with large differences being observed in the colostrum, transitional milk, and mature milk. Recently, researchers investigated the differences in cellular components, including stem cells, between colostrum and mature milk in preterm human milk (Kaingade, Somasundaram, Sharma, Patel, & Marappagounder, 2017). However, the study data were limited and were based on a small population, and the proportions of stem cells in preterm and term human milk throughout the stages of lactation were not compared.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that preterm mature milk has higher expressions of hematopoietic stem cells, mesenchymal stem-like cells, immune cells, some cell adhesion molecules and side-population cells than colostrum. Even if more studies are needed to support this pilot finding, a higher cell content in mature milk of preterm babies seems important in future health and growth outcomes [78]. Breast milk stem cells could therefore contribute to the modulation of numerous health outcomes associated with breastfeeding and offer potential innovative therapeutic approaches.…”
Section: Stem Cellsmentioning
confidence: 95%
“…Immunologically, human milk is usually suited to the gestational age at which a baby is born ( Espinosa-Martos et al, 2013 ; Kaingade et al, 2017 ). Colostrum and transient milk from mothers of very preterm infants seems to contain higher amounts of key immune compounds than those from mothers of term infants ( Montagne et al, 1999 ; Araujo et al, 2005 ; Koenig et al, 2005 ; Castellote et al, 2011 ; Espinosa-Martos et al, 2013 ; Moles et al, 2015b ), indicating that the degree of immunoprotection provided through breastfeeding is highly correlated with the immaturity degree of the neonate.…”
Section: Increasing Of the Use Of Omm In Nicus: Benefits And Challengmentioning
confidence: 99%